Implementasi Metode SAW Untuk Kepuasan Pelanggan Terhadap Pelayanan Pegawai Toko My Lova Kota Bengkulu - Niken Disriani; Sapri Sapri; Ila Yati Beti (UNIVED Press, 2025)
Toko My Lova in Bengkulu City is one of the retail businesses engaged in the sale of fashion products and accessories. Along with business development, the need for adequate service is very important. Customer satisfaction is one of the key factors that can determine the long-term success of this store. However, the problem that is often faced is the difficulty of evaluating the extent to which employee services affect the level of customer satisfaction, as well as how to improve the quality of services provided.The solution offered is the implementation of the SAW method to measure customer satisfaction with My Lova store employee services. The SAW method will be used to analyze various criteria that affect customer satisfaction, such as employee friendliness, service speed, product quality, store cleanliness, and others.The results of the analysis of 10 consumers who have been surveyed regarding their satisfaction with employee services at Toko My Lova Bengkulu City, using the SAW method, then 90% of consumers stated that they were very satisfied with the services provided by My Lova Store employees. and 10% of consumers stated that they were satisfied, with the service at the my lova shop.